Studi Kelayakan Sistem Pentanahan pada Gedung Teknik Elektro Universitas Andalas - Yudia Meka Seftiani; Novizon Novizon (Teknik Elektro Politeknik Negeri Padang, 2022)
The grounding system is one part of the electric power system that has an important role in flowing overcurrent from the electric power system to the ground due to electrical power system disturbances or lightning strikes that can endanger the building and its surroundings. This grounding system aims to protect humans, electrical equipment, and electrical installations from the danger of electrical short circuits. In compliance with official regulations, safety standards and according to general electrical installation regulatory standards (PUIL) to avoid the danger of lightning strikes in buildings, it is necessary to have grounding resistance value of less than five ohms and is made as small as possible. In this study, the measurement of grounding resistance seen from the depth of the grounding and the grounding resistance are arranged in parallel. The results of this study indicate that the parallel grounding resistance method produces a more significant reduction in the value of grounding resistance compared to the grounding resistance in a certain depth From the calculation results, the resistance value of the Electrical Engineering Building at Andalas University using a rod electrode with a diameter of 0.016 meters is 24.5 Ω with an electrode depth of 0.5 meters and at a depth of 1 meter a grounding value of 17.52 Ω is obtained. The deeper the depth of the electrode, the smaller the resulting resistance value, and installing a grounding system with the multirod method, namely arranging electrodes in parallel with a certain depth, obtains less resistance compared to not parallelizing the electrodes